3D skin models for 3R research: The potential of 3D reconstructed skin models to study skin barrier function. Issue 5 (6th April 2018) - Niehues, Hanna; Bouwstra, Joke A.; El Ghalbzouri, Abdoelwaheb; Brandner, Johanna M.; Zeeuwen, Patrick L. J. M.; van den Bogaard, Ellen H.
Abstract: The skin barrier is an important shield regulating the outside‐in as well as inside‐out penetration of water, nutrients, ions and environmental stimuli. We can distinguish four different barrier compartments: the physical, chemical, immunological and microbial skin barrier. Well‐functioning of those is needed to protect our body from the environment. To better understand the function and the contribution of barrier dysfunction in skin diseases, 3D skin or epidermal models are a valuable tool for in vitro studies. In this review, we summarize the development and application of different skin models in skin barrier research. During the last years, enormous effort was made on optimizing these models to better mimic the in vivo composition of the skin, by fine‐tuning cell culture media, culture conditions and including additional cells and tissue components. Thereby, in vitro barrier formation and function has been improved significantly. Moreover, in this review we point towards changes and chances for in vitro 3D skin models to be used for skin barrier research in the nearby future.